PENGARUH VARIABEL EKONOMI DAN VARIABEL DEMOGRAFI TERHADAP TINGKAT PENGANGGURAN ENAM PROVINSI DI INDONESIA: The Effect Of Economic Variables And Demographic Variables On The Level Of Unemployment In Six Provinces In Indonesia - Debby Nindya Istiandari (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – The purpose of this study was to analyze the effect of the economic variable and demography variable on the rate of unemployment in six provinces in Indonesia. Design/methodology/approach – This study uses a quantitative method with the type of data is time series secondary data from 2009 to 2018 and cross data from six provinces in Indonesia, which include DKI Jakarta Province, West Java Province, Central Java Province, DI Yogyakarta Province, East Java Province, and Banten Province. The data analysis technique used is panel data regression analysis, while the t-test was used for hypothesis testing. Findings – Based on the results of analysis, it was found that: 1) With the direction of the negative relation GRDP of the primary sector and GRDP of the secondary sector had an insignificant effect, while the GRDP of the tertiary sector had a significant effect on the rate of unemployment; and 2) with the direction of the positive relation population growth has a significant effect on the rate of unemployment. Research limitations/implications – Because the inflow of migration in the provinces of Java Island is high and the productive-age population in the provinces of Java Island is large, the government can implement a policy to maximize the absorption of the labor force that comes from regions on the island of Java, with the policy in question taking the form of a higher percentage of local male labor in all economic sectors. Originality/value – The objective is to balance the amount of employment with the number of employees. Still, it will also be beneficial to maximize the equitable distribution of the people in Indonesia so that economic growth is also more equal. Keyword : GRDP, Population Growth, Unemployment